Hubungan Higiene Personal terhadap Kejadian Pitiriasis Versikolor pada Mahasiswa Laki-laki Fakultas Kedokteran Unsrat - Tumilaar, Jibrando; Suling, Pieter L.; Niode, Nurdjannah J. (e-CliniC, 2019)
Abstract: Pityriasis versikolor is a skin fungal infection that is quite common in Indonesia as a tropical country with a hot and humid climate, especially if the personal hygiene is not good enough. This study was aimed to evaluate the relationship between personal hygiene and the incidence of pityriasis versicolor among male students of the Faculty of Medicine, Sam Ratulangi University. This was a descriptive analytical stuudy with a cross-sectional design. Subjects were 42 medical students of batch 2015-2018. Personal hygiene was determined by using questionnaires and diagnosis of pityriasis versicolor was confirmed based on clinical and Wood lamp examinations. The results showed that pityriasis versicolor was diagnosed in two subjects (4.8%). The Fisher’s exact test obtained a significancy value of 0.003 which indicated that there was a significant relationship between personal hygiene and pityriasis versicolor. Conclusion: There was a significant relationship between personal hygiene and the occurence of pityriasis versicolor. Poor personal hygiene was a risk factor of pityriasis versicolor.Keywords: pityriasis versicolor, personal hygiene, students Abstrak: Pitiriasis versikolor adalah infeksi jamur kulit yang cukup banyak ditemukan di Indonesia yang merupakan negara tropis beriklim panas dan lembab, apalagi bila higiene kurang sempurna. Penelitian ini bertujuan untuk mengetahui higiene personal terhadap kejadian pitiriasis versikolor pada mahasiswa laki-laki Fakultas Kedokteran Universitas Sam Ratulangi. Jenis penelitian ialah deskriptif analitik dengan desain potong lintang. Subjek penelitian ialah 42 mahasiswa Kedokteran Umum angkatan 2015-2018. Tingkat higiene personal diambil dari kuesioner dan diagnosis pitiriasis versikolor ditegakkam berdasarkan pemeriksaan klinis dan lampu Wood. Hasil penelitian memperlihatkan kejadian pitiriasis versikolor pada dua subyek penelitian (4,8%). Uji Fisher’s exact test mendapatkan nilai signifikansi 0,003 yang menunjukkan adanya hubungan bermakna antara higiene personal dan pitiriasis versikolor. Simpulan: Terdapat hubungan bermakna antara higiene personal dan pitiriasis versikolor. Higiene personal yang buruk merupakan faktor risiko terjadinya pitiriasis versikolor.Kata kunci: pitiriasis versikolor, higiene personal, mahasiswa